Graphics' design work: event / Noorza Fatihah Zakaria - Zakaria, Noorza Fatihah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The Miri Tattoo Festival (MTF) is an event held in Miri, Sarawak. The festival exhibits activities such as tattoo beauty contests, Dayak Material art showcases, and traditional parades. To be highlighted as a tourist attraction. MTF needs to improve its branding. The festival combines conventional Sarawak tattoos with contemporary aesthetics, employing print and digital advertisements to endorse its brand. The MTF's logo is designed according to the Sarawak tattoo motif and incorporates innovative ideas of modern concept. multimedia platforms, including the creation of commercial videos and booth designs for events will also be incorporated.